XvGoIS, a galactinol synthase is transcriptionally upregulated under water deficit : the role of raffinosaccharides in abiotic stress tolerance in the resurrection plant Xerophyta viscosa (Baker) - Peters, Shaun W (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (leaves 84-102).